Fuzzy cγ-open sets and fuzzy cγ-continuity in fuzzifying topology - T. Noiri; O. R. Sayed (International Journal of Mathematics and Mathematical Sciences)
The concepts of fuzzy cγ-open sets and fuzzy cγ-continuity are introduced and studied in fuzzifying topology and by making use of these concepts, some decompositions of fuzzy continuity are introduced.